Pengaruh Good Corporate Governance (GCG) terhadap Kinerja Keuangan Perbankan di Indonesia (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI tahun 2017-2021) - Faris Salman Alfarizi; Usep Syaifudin; Ade Widiyanti; Ratna Septiyanti (Departement of Mathematics Education, 2024)
The implementation of Good Corporate Governance is considered to be able to improve the bad image of banking, protect stakeholders and increase compliance with applicable laws and regulations and general ethics in the banking industry in order to image a healthy banking system. Apart from that, the implementation of Good Corporate Governance in banking is expected to have an influence on banking performance because the implementation of Corporate Governance can improve financial performance, reduce risks due to management actions that tend to benefit oneself. The independent variable in this research is Good Corporate Governance which is measured by the indicators of the Board of Commissioners, Board of Directors and Audit Committee. The dependent variable is a type of variable that is explained or influenced by the independent variable. The dependent variable in this research is banking financial performance as measured by ROA. The population in this research is all public banking companies listed on the Indonesian Stock Exchange for the 2017-2021 period (43 banking companies). In this research, the samples used and included in the criteria were 25 companies. This research uses secondary data obtained from annual reports of banking companies listed on the Indonesia Stock Exchange (BEI) during the 2017-2021 period. This research uses the Classic Assumption Test and Multiple Linear Regression Test.